The Pro Bono Legal Aid in Religious Courts and the Constitutional Right to Equality Before the Law: Toward Collective Accountability of Law Enforcement Officers - Nikyta Tsabita Khansa; Syaghaf Muhammad Sa’ad; Maulana Iqbal; Musleh Harry (Journal of Indonesian Islamic Studies, 2025)
Access to justice in Indonesia’s Religious Courts remains structurally constrained, particularly for low-income litigants who frequently navigate divorce, child custody, and inheritance disputes without adequate legal representation. Despite a comprehensive normative framework grounded in Articles 27(1) and 28D (1) of the 1945 Constitution, Law Number 16 of 2011 on Legal Aid, Law Number 50 of 2009 on Religious Courts, and Supreme Court Regulation Number 1 of 2014 concerning Legal Aid Posts (Posbakum), the substantive realization of the constitutional right to equality before the law remains limited in practice. This study examines the constitutional urgency of pro bono legal aid provision in Religious Courts and analyzes how the collective responsibility of law enforcement officers should be conceptualized to ensure its effective implementation. This study employed a normative juridical method using statute and conceptual approaches, supported by primary legal materials, regulatory documents, and scholarly literature. The findings reveal three main points. First, pro bono legal aid constitutes a constitutional obligation rather than a discretionary service, as substantive equality before the law requires the removal of economic, geographic, and informational barriers to justice. Second, the implementation gap in Religious Courts is primarily caused by fragmented institutional responsibility, limited budget allocation, uneven distribution of accredited legal aid institutions, and weak accountability mechanisms. Third, effective legal aid provision requires an integrated collective responsibility framework involving judges, advocates, legal aid institutions, and court registrars as interdependent actors in ensuring access to justice. This study contributes to the literature by reframing pro bono legal aid in Religious Courts as a constitutionally mandated collective responsibility essential to fulfilling equality before the law.